Elementary School Teachers’ Self-Efficacy Toward Teaching Writing - Amatullah, Ummu Fauziyyatun; Iswara, Prana Dwija (International Conference on Elementary Education, 2022)
Writing is an essential aspect of language learning and for the language skills needs of elementary school students. However, the self-efficacy of elementary school teachers towards teaching writing is known by little. Teachers' self-efficacy towards teaching writing affects their perceptions and judgments, influencing instructional decisions during student learning activities. This study aimed to describe elementary school teachers’ self-efficacy in teaching writing in the classroom. This research was completed by a quantitative approach with a survey method of 13 elementary school teachers. The research’s results indicate that the self-efficacy of elementary school teachers on writing lessons is still not optimal. Almost all teachers (11 out of 13) were at the 61-70% self-efficacy in teaching writing. 1 out of 13 teachers has achieved 60% self-efficacy in learning to write along with the percentage of self-efficacy of elementary school teachers in teaching writing. And only one teacher who has a level of > 70% self-efficacy in learning to write. Changing writing practice in elementary school will require individualized instructional methods to meet student needs as well as the personal assessment of self-efficacy to ensure that beliefs do not hinder the delivery of effective instructional writing practices.